A cross-sectional analysis of occupational stress and mental health among migrant healthcare workers in Ireland - Sindhu Thankachen; Zubair Kabir; Anvar Sadath (Journal of Migration and Health)
Background: The migration of healthcare workers (HCWs) to European countries has witnessed a recent increase in both number and diversity. While facing various socio-cultural challenges in the host country, it becomes imperative to investigate the mental health of these workers, given the significance for their well-being and the safety of patients. This study aims to assess the extent of occupational stress and psychological distress among migrant healthcare workers in Ireland, along with exploring the contributing factors. Methods: A cross-sectional online survey, utilizing Google Forms, was conducted via social media platforms among overseas nursing and Healthcare Assistants currently employed in the Republic of Ireland. Occupational stress and psychological distress were assessed using the Brief Job Stress Questionnaire (BJSQ) and the Kessler Psychological Distress Scale (K6). Multivariable linear regression models were employed to identify significant predictors of occupational stress and psychological distress. Results: The response rate was 35.8 (n = 447) from 1250 invitees. The majority of participants were nurses (93 %), largely from India (72.7 %), followed by the Philippines (17.7 %). The healthcare workers reported moderate to high job stress, with elevated scores in quantitative overloads, mental demands at work, and physical work demands. Migrant healthcare workers with <10 years of work experience in Ireland perceived higher job stress (t = 2.826; β = 0.154; p = 0.005) and psychological distress (t = 5.666; β = 0.303; p = 0.000). Working in private healthcare sectors was associated with a lower perception of job stress (t = -3.077; β = 0.15; p = 0.002) and psychological distress (t = -2.643; β = 0.126; p = 0.009). Conclusion: The findings highlight that HCWs experience moderate to high job stress, particularly those with <10 years of experience. Psychological distress was also prevalent, with private-sector employment associated with lower stress levels. These results emphasize the need for targeted interventions to support migrant HCWs’ well-being.